PENGEMBANGAN PROTOTIPE BUKU PENDIDIKAN EKOLOGIS MELALUI SENI DRAMA UNTUK KELAS V SD (BUKU GURU) - Ignatia Esti Sumarah; Ignatius Loyola Madya Utama S.J.; Kristophorus Divinanto Adi Yudono (Universitas Katolik Indonesia Atma Jaya, 2019)
Since 1996 Directorate General of Ministry of Elementary and Secondary Education has been emphasizing the importance of giving ecological education so that pupils will have concern for caring and keeping the integrity of creation. This is in line with the teaching of the Catholic Church, which is strengthened by Pope Francis in his encyclical letter, Laudato Si’, published on May 24, 2015. From answers to questionnaires distributed to five Catholic teachers teaching at urban schools can be concluded that (1) ecological spirituality should become foundation of ecological education, (2) themes on ecological education found in elementary school thematic lessons should be understood as efforts to build ecological morality, and (3) the need for providing an example of a drama script which can be used by teachers as a method of teaching materials on ecological education. This research aimed at developing a book prototype entitled Caring for the Earth as Our “Common Home”: A Reflection on Encyclical Letter Laudato Si’ (for Elementary School Teachers). This book prototype has articles on ecological spirituality and ecological education as well as a drama script which can be used by teachers of fifth grade to teach third theme “Healthy Food,” second sub-theme “The Importance of healthy food for human body.” The development of this book prototype utilizes five of ten steps of Research and Development according to Borg & Gall: (1) analyzing the needs of developing a book prototype of ecological education, (2) studies on ecological education found in thematic lessons at elementary school, (3) developing a book prototype, (4) validation of the book prototype, and (5) revision of the book prototype. Findings of the research showed that the book prototype could be published. This was shown by evaluation given by a lecturer of biology with a mean score of 3.5 and evaluation given by a five grade teacher with a mean score 3.75. These mean scores are very high.